Fluorescent probes based on side-chain chlorinated benzo[a]phenoxazinium chlorides: studies of interaction with DNA - Raju, B. Rama (2017)
The interaction of DNA with six water soluble benzo[a]phenoxazinium chlorides mono- or di-substituted with 3-chloropropyl groups at the O and N of 2- and 9-positions, along with methyl, hydroxyl and amine terminal groups at 5-positions, was investigated by photophysical techniques. The results indicated that almost all compounds intercalated in DNA base pairs at phosphate to dye ratio higher than 5. At lower values of this ratio, electrostatic binding mode with DNA was observed. Groove binding was detected mainly for the benzo[a]phenoxazinium dye with NH2.HBr terminal. The set of six benzo[a]phenoxazinium chlorides proved successful to label the migrating DNA in agarose gel electrophoresis assays. These finding proves the ability of these benzo[a]phenoxazinium dyes to strongly interact with DNA.